SEISMIC ATTENUATION TOMOGRAPHY USING MICROEARTHQUAKE DATA CASE STUDY: ÃâÃâANÃâÃâ GEOTHERMAL FIELD - NUR AULIA (NIM : 22316018), ATIN
The existence of volcano due to subduction in Java causes Indonesia to have high geothermal potential, one of them in “AN” geothermal field. Injection and production processes in geothermal areas causing the occurrence of microearthquakes that have relatively small magnitudes and shallow depths. Research on 3-D velocity tomography and anisotropy analysis has been successfully performed in the “AN” geothermal field. However, some important physical properties of rocks have a relatively greater effect in attenuation than in velocity, therefore, this study discusses the inversion of attenuation tomography (1/Q). A total of 755 micro earthquake data were used in this study with S and P phases of 4526 each phases. The data required for tomographic inversion are the attenuation operator t* and the 3-D velocity model obtained from the previous study. The attenuation operator is determined using spectral fitting method. The t* data of P wave obtained as many as 2936 data from 579 microearthquakes while for S wave obtained data t* as many as 2931 data from 507 microearthquakes. The results of the attenuation tomography inversion in this study are expected to provide additional information to strengthen the interpretation of reservoir characterization that has been done in previous research. High Qp/Qs and High Vp/VS around Mt. Gambung and Mt. Bedil interpreted as fully saturated brine at depth more than 0 km. Low Qp/Qs and Low Vp/VS interpreted as partial saturated dominated steam. There is a corresponding high Qp /Qs anomaly with straightness based on Landsat imagery may be associated with the structure that divided high permeability zone and low permeability zone.